POST-APARTHEID REFLECTIONS ON CRITIQUE, TRANSFORMATION AND REFUSAL (The Pretoria Student Law Review, 2021)
In this article I engage with the notion of refusal, as introduced by Karin Van Marle, to post-apartheid jurisprudence as a way through which to think of life, death, law and politics against the backdrop of poverty, social misery, disease, oppression and prejudice. She proposes that we consider refusal firstly as a possible mode of critical thinking and theorising but ultimately also as an alternative approach to law and jurisprudence. For Van Marle, what lies at the heart of refusal is the ‘idea of unexpectedness that breaks with the formality and predictability of law’ — an unexpectedness that could disclose new directions for thinking about and doing law.
Keywords: notion of refusal; post-apartheid jurisprudence; Karin Van Marle; formality and predictability of law